Comparative Analysis of Telomere Length, Telomerase and Reverse Transcriptase Activity in Human Dental Stem Cells - Byeong-Gyun Jeon (Cell Transplantation, 2011)
Stem cells from dental tissues have been isolated and established for tooth regenerative applications. However, basic characterization on their biological properties still needs to be investigated before employing them for effective clinical trials. In this study, we compared the telomere length, relative telomerase activity (RTA), and relative reverse transcriptase activity (RRA) as well as the surface antigen profile and mesenchymal differentiation ability in human dental papilla stem cells (DPaSCs), dental pulp stem cells (DPuSCs), and dental follicle stem cells (DFSCs) with mesenchymal stem cells (MSCs) derived from bone marrow. Dental stem cells (DSCs) were strongly positive for cell surface markers, such as CD44 and CD90. However, slightly lower expression of CD105 was observed in DPaSCs and DPuSCs compared to DFSCs and MSCs. Following specific induction, DPaSCs, DFSCs, and MSCs were successfully differentiated into adipocytes and osteocytes. However, DPuSCS, in particular, were able to differentiate into adipocytes but failed to induce into osteogenic differentiation. Further, all DSCs, MSCs, and MRC-5 fibroblasts as control were investigated for telomere length by nonradioactive chemiluminescent assay, RTA by relative-quantitative telomerase repeat amplification protocol (RQ-TRAP), and RRA by PCR-based assay. Mean telomere lengths in DPaSCs, DPuSCs, DFSCs, and MSCs was ~11 kb, and the values did not differ significantly ( p < 0.05) among the cells analyzed. RTA levels in DPaSCs were significantly ( p < 0.05) higher than in MSCs, DPuSCs, DFSCs, and MRC-5 fibroblasts and among DSCs, DFSCs showed a significantly ( p < 0.05) lower RTA. Moreover, RRA levels were significantly ( p < 0.05) higher in DPaSCs, DPuSCs, and MSCs than in DFSCs. Based on these observations, we conclude that among DSCs, DPaSCs possessed ideal characteristics on telomere length, telomerase activity and reverse transcriptase (RTase) activity, and may serve as suitable alternative candidates for regenerative medicine.